From progressivism to bourgeois conservatism. A comparative analysis of La Cenerentola, by Rossini, and Cendrillon, by Massenet - Orlante, Emiliano (2021)
This article sets out to explore the relation between Charles Perrault's and the Grimm brothers' Cinderella and the operas' La Cenerentola (1817), by Gioachino Rossini (1792-1868), and Cendrillon (1894/5), by Jules Massenet. Given the temporal and geographic distance between the texts and their difference in terms of genre -fairytale and opera, this paper adopts a comparative methodology of the study. This methodological approach allows to analyze the literary meanings constructed by each piece and the bonds between them, without ignoring contextual and stylistic aspects. Studying these relations makes it possible to pose the following hypothesis: whereas Cendrillon emerges as a musical expression of the conservative bourgeoisie, La Cenerentola reveals its enlightened dimension through artistic devices.